2013
DOI: 10.1002/syn.21717
|View full text |Cite
|
Sign up to set email alerts
|

A selective sigma‐2 receptor ligand antagonizes cocaine‐induced hyperlocomotion in mice

Abstract: Cocaine functions, in part, through agonist actions at sigma-1 (σ1 ) receptors, while roles played by sigma-2 (σ2 ) receptors are less established. Attempts to discriminate σ2 receptor-mediated effects of cocaine in locomotor hyperactivity assays have been hampered by the lack of potent and selective antagonists. Certain tetrahydroisoquinolinyl benzamides display high σ2 receptor affinity, and excellent selectivity for binding to σ2 over σ1 receptors. The behavioral properties of this structural class of σ lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 58 publications
4
31
1
Order By: Relevance
“…Animals were euthanized, and tissue radioactivity was determined 30 minutes after intravenous administration of [ 125 I]E-IA-DM-PE-PIPZE. As expected from previous work (Lever et al, 2012(Lever et al, , 2014, significant blockade of uptake by BD1063 (5.0 mmol/kg i.v.) in brain (84%), heart (58%), spleen (70%), and lung (68%) was observed.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Animals were euthanized, and tissue radioactivity was determined 30 minutes after intravenous administration of [ 125 I]E-IA-DM-PE-PIPZE. As expected from previous work (Lever et al, 2012(Lever et al, , 2014, significant blockade of uptake by BD1063 (5.0 mmol/kg i.v.) in brain (84%), heart (58%), spleen (70%), and lung (68%) was observed.…”
Section: Resultssupporting
confidence: 90%
“…PD144418 displayed an ED 50 of 0.22 mmol/kg in whole mouse brain, and ED 50 values ranging from 0.08 to 0.39 mmol/kg in heart, lung, and spleen. In a directly comparable study (Lever et al, 2014), BD1063 administered intraperitoneal gave an ED 50 of 0.62 mmol/kg in mouse brain, with ED 50 values between 0.14 and 1.47 mmol/kg for the heart, lung, and spleen.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Several studies have shown that cocaine preferentially exert its psychostimulant effect by binding to sigma-1 receptors. It is believed that, sigma-1 receptors influence the actions of cocaine through three different mechanisms, 1) direct binding to the receptors, 2) modulation of other neurotransmitter systems, and 3) alterations in gene expression [34,35]. Matsumoto et al confirmed that low doses of novel sigma receptor antagonists could notably inhibit convulsions and lethality induced by toxic doses of cocaine.…”
Section: Sigma Receptor Ligandsmentioning
confidence: 99%